MICROWAVE-ASSISTED TECHNIQUE FOR BIODIESEL PRODUCTION FROM CEIBA PENTANDRA SEED OIL - LIEU , THI NGOC THANH (2015)
The continual use of fossil fuels has caused serious detrimental impacts on environment as well as human life. Biodiesel as a renewable energy resource has shown a positive effect on resolving environmental problems and helping to fulfil energy demand in the future. Due to economic and social concerns, the use of edible vegetable oils should be replaced by non-edible plant oils for biodiesel production. Thus, the oil from tropical plant Ceiba Pentandra is an attractive potential feedstock. Nowadays, a great attention has been paid to advanced microwave technology, a potential means to markedly enhance the biodiesel production process. In this study, response surface methodology (RSM) based on central composite design (CCD) was employed to investigate the influence of four process parameters, i.e. catalyst concentration, methanol to oil molar ratio, temperature and time on the response, and optimum conditions towards the reduction of free fatty acids (FFA) and conversion of biodiesel under microwave irradiation.